Relationship between surface microstructure and properties of supported catalyst Rh/Ys - 柳忠阳 潘平来 朱长城 王晓筠 袁国卿 (Science China. Chemistry, 1997)
The inner structure of Rh/Ys,a novel high efficiency supported catalyst,and the spreading of Rh on the Ys surface were analyzed through electron transmission microscopy and scanning tunnel microscopy.The relationship between the distribution of Rh over the support and the preparation temperature of th catalyst was determined.The formation of Rh-C bond was confirmed by XPS and far-IR spectra.The loss of Rh from the surface of the support and the catalytic activity under different preparation conditions have been compared.The internal factors for the high activity and high stability of the novel Rh/Ys catalyst have been discussed.